Finanzierung von Staatsaufgaben: Nachhaltige Finanzpolitik und Schuldenbremse - Rudi Kurz (Wirtschaftsdienst, 2024)
– Multiple crises and ecological transformation are driving an intense debate about government credit financing and its restriction by the constitutional debt brake. The Board of Academic Advisors at the BMWK has presented a proposal on how more flexibility would be possible without undermining the indispensable disciplining function of the debt brake. The Board recommends a selective relaxation of the debt brake linked to conditions that are virtually impossible to fulfil (net investment, independent institution, no inflationary effects). Therefore, regarding the fact that the Board has formulated a justification for the debt brake: As long as there is no practicable reform proposal, there is no reason to change the constitution.
Keywords: H50; H60; Q01; 330; Finanzpolitik; Öffentliche Schulden; Deutschland; Finanzpolitik; Öffentliche Schulden; Deutschland